Reinventing HCV Treatment: Past and Future Perspectives. (4th November 2016) - Carter, Wendy; Connelly, Sarah; Struble, Kimberly
Abstract: This review paper summarizes the epidemiology of hepatitis C virus (HCV) and chronic HCV infection, including HCV virology and treatment regimens. Specifically, we focus on the evolution of past, current, and future HCV treatment options, the reasons for treatment failure, and the impact of resistance‐associated variants on treatment success.